Konsep Pendidikan Profesional Perspektif Undang-Undang tentang Guru dan Dosen - Eti Sutarsih; M Misbah (Jurnal Kependidikan, 2021)
Abstract Educators must have an attitude in dealing with students so that they are in accordance with the teachings conveyed by Islam. Educators need to know and be aware of the profession that is taken as a calling for the soul to be able to achieve a maximum learning goal, they need to know and practice several tasks as professional educators. Professional educators are regulated in the Law on Teachers and Lecturers. Therefore, it is important for an educator to learn and implement it to become a professional educator. This research uses descriptive analysis method. This type of research is carried out on national and international literature review sources related to the concept of professional educators. Professional educators must carry out their duties as educators as stated in the law on teachers and lecturers. Professional educators must have educator competencies in carrying out their responsibilities in educating, teaching, guiding, assessing, training, and evaluating students. In addition, the quality of an educator will continue to improve, which in the end, the quality of educational institutions will also have quality. Professional educators will continue to strive to develop themselves according to the times. Has the nature and character that is in accordance with the duties or obligations as an educator Keywords Educators, Professional, and Law Abstrak Pendidik harus memiliki sikap dalam menangani peserta didik agar sesuai dengan ajaran yang disampaikan oleh agama Islam. Pendidik perlu mengetahui dan sadar akan profesi yang diambil sebagai panggilan jiwa untuk dapat mencapai sebuah tujuan pembelajaran yang maksimal perlu mengetahui dan mengamalkan beberapa tugas sebagai pendidik professional. Pendidik profesional sudah diatur dalam Undang-Undang tentang Guru dan Dosen. Oleh karena itu, pentingnya seorang pendidik mempelajari dan melaksanakan untuk menjadi pendidik yang profesional. Penelitian ini menggunakan metode analisis deksriptif. Jenis penelitian yang dilakukan pada sumber-sumber kajian pustaka nasional maupun internasional yang berhubungan dengan konsep pendidik profesional. Pendidik profesional harus menjalankan tugas sebagai pendidik yang telah tercantum di dalam undang-undang tentang guru dan dosen. Pendidik profesional harus memiliki kompetensi-kompetensi pendidik dalam menjalankan tanggung jawab dalam mendidik, mengajar, membimbing, menilai, melatih serta mengevaluasi peserta didik. Selain itu, kualitas yang dimiliki seorang pendidik akan terus meningkat yang pada akhirnya kualitas lembaga pendidikan juga akan ikut bekualitas. Pendidik profesional akan terus berusaha untuk mengembangkan diri sesuai dengan perkembangan zaman. Memiliki sifat dan karakter yang sesuai dengan tugas atau kewajiban sebagai pendidik. Kata Kunci Pendidik, Profesional, dan Undang-Undang